2020
DOI: 10.18203/2349-2902.isj20204992
|View full text |Cite
|
Sign up to set email alerts
|

Is gender a determinant for the outcome of laparoscopic cholecystectomy?

Abstract: Background: Currently, laparoscopic cholecystectomy is one of the most desirable procedures to treat symptomatic gallstone disease. Yet, various risk factors govern its conversion to open surgery. The impact of male sex as a risk factor for conversion has been a questionable issue.  The study aimed to evaluate the role of male sex on outcomes of laparoscopic cholecystectomy.Methods: As per inclusion and exclusion criteria, medical records of all the patients aged 18-70 years who underwent elective LC for a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…13 A Bahadur et al in 2020 in similar study suggested that male gender is not an independent risk factor for conversion in laparoscopic cholecystectomy. 14 In our study we observed 7 male patients and 3 female patients ( p= 0.203) had conversion to open during the procedure drawing similar inference that there is no significant association of male gender as risk factor for conversion. In our study mean operating time in male gender was significantly higher than female gender, p value 0.516 however this was not significant.…”
Section: Discussionsupporting
confidence: 73%
“…13 A Bahadur et al in 2020 in similar study suggested that male gender is not an independent risk factor for conversion in laparoscopic cholecystectomy. 14 In our study we observed 7 male patients and 3 female patients ( p= 0.203) had conversion to open during the procedure drawing similar inference that there is no significant association of male gender as risk factor for conversion. In our study mean operating time in male gender was significantly higher than female gender, p value 0.516 however this was not significant.…”
Section: Discussionsupporting
confidence: 73%